The Influence of the Sherman STEM Teacher Scholars Program on Persistence in Science, Technology, Engineering, and Mathematics: A Mixed-Methods Study - Ramon B. Goings; Brittany Boyd (MDPI AG, 2024)
This sequential explanatory mixed-methods study investigated the differences in persistence between students from the Sherman STEM Teacher Scholars Program (STEP), a STEM teacher scholarship and career preparation program, and STEM majors not in the program. Quantitative results indicated that STEP participants had higher levels of academic integration, women scored higher on persistence factors than men, and White students had a higher degree commitment than students of color. Qualitative findings indicated that STEP provided a family atmosphere and connected their coursework to their career aspirations. Women of color felt stereotyped by White classmates in STEM courses, which impacted their degree of commitment, and students of color in STEP relied on the program as a counterspace to racially insensitive STEM classrooms.